2012
DOI: 10.1149/2.054204jes
|View full text |Cite
|
Sign up to set email alerts
|

Interionic Energy Transfer in Y3Al5O12: Ce3+, Pr3+, Cr3+Phosphor

Abstract: We present an investigation of dynamical processes of nonradiative energy transfer (ET) in Y 3 Al 5 O 12 :Ce 3+ , Pr 3+ , Cr 3+ phosphor. The analysis based on Inokuti-Hirayama model indicates that the ET from the lowest 5d state of Ce 3+ to the 4 T 2g state of Cr 3+ , and from the state 1 D 2 of Pr 3+ to 4 T 2g state of Cr 3+ are both governed by electric dipole-dipole interaction. For Pr 3+ concentration of 0.005 in YAG: Pr 3+ Cr 3+ and for Ce 3+ concentration of 0.01 in YAG: Ce 3+ Cr 3+ the rate constant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…(a)] and PLE spectrum of Pr 3+ [Fig. (b)], which would enable an efficient energy transfer from Ce 3+ to Pr 3+ according to the Förster's model . For the Ce 3+ , Pr 3+ codoped sample [Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a)] and PLE spectrum of Pr 3+ [Fig. (b)], which would enable an efficient energy transfer from Ce 3+ to Pr 3+ according to the Förster's model . For the Ce 3+ , Pr 3+ codoped sample [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 (b)], which would enable an efficient energy transfer from Ce 3+ to Pr 3+ according to the F€ orster's model. [30][31][32] For the Ce 3+ , Pr 3+ codoped sample [ Fig. 4 (c)], Pr 3+ : 1 D 2 ?…”
Section: August 2014mentioning
confidence: 99%
“…Wang et al. reported that the emission intensity at 610 and 640 nm of YAG:Ce phosphors could be enhanced by adding Pr 3+ as the codopant, whereas the Ce 3+ emission intensity was decreased because of the transfer of energy from Ce 3+ to Pr 3+ …”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported that the emission intensity at 610 and 640 nm of YAG:Ce phosphors could be enhanced by adding Pr 3+ as the codopant, whereas the Ce 3+ emission intensity was decreased because of the transfer of energy from Ce 3+ to Pr 3+ . [1][2][3] The red components of YAG:Ce can also be enhanced by increasing the crystal field strength of Ce 3+ . It is known that the d-orbital splitting of Ce 3+ caused by the crystal field strength is inversely proportional to the Ce-ligand bond length to its fifth power, and therefore the red-shift of the emission band of YAG:Ce may occur with a reduction in the bond length between Ce and ligand ion.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, Cr 3+ ion is an efficient electron trap [27]. As the charge transfer O 2− →Cr 3+ band lies at 230 nm [28], just above the self trapped exciton emission, it is therefore reasonable that ionization can occur more likely for Cr 3+ in a excited state than in ground state. As the current injection increases, more Cr 3+ ions are excited from the ground state 4 A 2 into the metastable manifold 2 E. The host excitons more likely give up their energy in the O 2− →Cr 3+ charge transfer rather than in the direct excitation Ho 3+ ions or in the radiative decay.…”
Section: Appendix a Saturation Behaviourmentioning
confidence: 99%